Unveiling the role of hypertrophic chondrocytes in abnormal cartilage calcification: insights into osteoarthritis mechanisms - JP Yao; J Xu; ZN Huo; YP Yi; DM Xu; XF Wang; JJ Shang; Y Huang; YP Weng; XD Zhou (European Cells & Materials, 2024)
Osteoarthritis (OA) is a chronic degenerative disease that affects the whole joint, especially the knee joint. Its main features include articular cartilage defects and osteophyte formation, and it is common in middle-aged and elderly people. Although the pathogenesis of OA is not fully understood, mechanical factors, inflammation and immune abnormalities can affect joint tissue metabolism and destroy cartilage and bone homeostasis. Cartilage calcification is closely related to chondrocyte hypertrophy, differentiation and bone sclerosis in OA, which is manifested as pathological calcification of cartilage matrix. Chondrocytes in OA may change from a state of maintaining cartilage matrix balance to a state of promoting cartilage destruction and calcification. Inflammatory factors such as TNF-α and IL-1β promote this phenotypic shift, accelerating matrix degradation and calcium salt deposition. The change of calcium signal and an important factor of angiogenesis and promote cartilage calcification. Chondrocyte hypertrophy plays a crucial role in the pathogenesis and progression of OA, characterized by complex interactions with cartilage calcification, subchondral bone sclerosis, as well as chondrocyte proliferation, apoptosis, matrix remodeling, and signaling cascades. The degree of chondrocyte hypertrophy exhibits a positive correlation with the severity of OA. Furthermore, structural changes in the articular cartilage are associated with factors including reduced cartilage collagen synthesis or the activation by degradative enzymes. Regulatory mechanisms governing chondrocyte hypertrophy and cartilage calcification, alongside the identification of pertinent genes, represent pivotal areas for future investigation. This research will further elucidate the pathogenesis of OA and lay the groundwork for devising therapeutic strategies.